PERAN DAKWAH ISLAMIYAH DALAM MEMBENTUK MASYARAKAT BERADAB DI TENGAH GLOBALISASI: STUDI KASUS DESA SUGIHARJO - Alfadhilah, Jauharotina; Rahmat Albustomi, Abdul; Zaman, Sa’di (Department of Da'wah Management, Faculty of Da'wah, IAINU Tuban, 2024)
Islamic da'wah plays a strategic role in spreading Islamic teachings in society, particularly in the aspects of faith, worship, morality, and social relations. In Sugiharjo village, Islamic da'wah has made a significant impact through various activities such as lectures, religious study groups, and the study of traditional Islamic texts (kitab kuning). This method of da'wah has successfully improved religious understanding, enhanced morality, and strengthened social and family harmony. However, in the era of globalization, da'wah faces challenges such as the influence of foreign cultures, limited access to technology, and resistance from traditional communities. To overcome these challenges, da'wah in Sugiharjo utilizes digital media, relevant religious education, and collaboration with social institutions. The locally based strategy, which is inclusive and adaptive to the times, has proven effective in building a religious and harmonious society.